The Critical Role of the Clinical Research Coordinator for Clinical Trials: A Survey in Oncology. Issue 1 (2017) - Cinefra, Margherita; Cagnazzo, Celeste; McMahon, Laura; Arizio, Francesca; Campora, Sara; Camisa, Roberta; Canzanella, Giuliana; Contu, Marianna; Frati, Paola; Sottile, Roberta; Gori, Stefania; Procopio, Giuseppe; et al.
Introduction: Access to innovative medicine requires proper evidence from clinical trials with the growing demand of qualified and experienced personnel. The clinical research coordinator (CRC) plays an important role in the conduction of research activities and provides a strong support to the research team. In Italy, this role is not recognized at any institutional level and its professional outline is still indefinite. Several national associations (Associazione Italiana di Oncologia Medica, Collegio Italiano dei Primari Oncologi Medici Ospedalieri, Gruppo Italiano Data Manager) are committed to promoting the enhancement and recognition of the professional status of CRCs, underlining their role as fundamental. Methods: A web survey, proposed by the AIOM CRC Working Group, was submitted to 319 Italian oncology sites with items focusing on the organization of sites, the research activities, the staff composition, and the presence of coordinators and the multidisciplinary team. Results: A total of 115 sites (35.9%) responded to the web survey. Clinical studies were carried out at 88.7% of the investigated sites, and coordinators were on staff at 75.5% of the active investigational sites. Interestingly, there was a direct association between the number of clinical studies and the number of coordinators, whose contribution to the research activities is believed to be essential for trial conduct in 82.4% of cases. Most sites retain that the quality of clinical research has absolutely improved (83.3%) after the implementation of a coordinator as member of the team. Conclusions: Given the constant growth of the number of clinical trials performed at Italian oncology sites, the CRC proves to be an essential component of the research team. However, there is an urgent need to institute the professional role alongside the need to standardize the training of coordinators to establish the minimum requirements enhanced by qualifying courses.